Market Capitalization- Sustainability Practices Measurement of Private Commercial Banks of Bangladesh - Sultana, Nasreen; Akter, Afroja (American Journal of Trade and Policy, 2017)
The study investigates the sustainability practices of the private commercial banks of Bangladesh to consider these as measurement of the market capitalization of the same. In the research 30, private commercial banks have been taken into consideration where it is found that market capitalization is not wholly dependent on the issue of sustainability and there is no long run relationship between market capitalization and sustainability issues which could have an impact on the market capitalization or any direction of the market capitalization. Rather Granger Causality result shows that market capitalization could have an impact on the sustainability issues of the banks. The inclusion of some other explanatory variables in the model could deduce a better conclusion.